Varus strength of the medial elbow musculature for stress shielding of the ulnar collateral ligament in competitive baseball pitchers - Yanai, T.; Onuma, K.; Nagami, T. (Medicine & Science in Sports & Exercise, 2025)
Purpose Valgus load opens the medial elbow compartment, causing elongation of the ulnar collateral ligament (UCL) that can eventually lead to attenuation and failure. Ideally, the muscles surrounding the medial aspect of elbow joint should coordinate medial elbow compression to prevent the medial elbow compartment from opening and loading the UCL. This study aimed to determine whether baseball pitchers have sufficient elbow varus strength to unload the UCL during pitching.